A flexible cofactor‐binding loop in the novel arginine methyltransferase Sfm1. Issue 2 (28th December 2016) - Wang, Caiyan; Zeng, Jianhua; Xie, Wei
Abstract : Arginine methylation is a common post‐translational modification and is critical for many cellular processes. Sfm1 is a novel arginine methyltransferase that contains a SpoU‐TrmD (SPOUT) domain, a typical fold known for RNA methylation, but acts on a ribosomal protein. The underlying mechanism is poorly understood. Here, we report cocrystal structures of Sfm1 in complex with various ligands. We found that a critical loop responsible for S ‐adenosyl‐l ‐methionine (SAM) binding adopts a different conformation from previous reports, and SAM appears to exhibit double conformations. Deletion of this loop greatly reduces the affinity of Sfm1 to SAM. Additionally, by comparison to closely related tRNA‐methyltransferase Trm10, our structural analyses offer a good explanation why the two enzymes utilize distinct substrates, providing insights into the molecular mechanism. Abstract :